THE RELATIONSHIP BETWEEN SMOKING HABIT AND DECREASE IN SALIVARY FLOW RATE - Dwi Septian Wijaya (Perhimpunan Kesehatan Holistik Indonesia, 2020)
Smoking is an addictive habit and is an important factor that can cause various diseases and even death. The dangers of smoking on the health of the body have been proven by many researchers. Smoking can affect the physiology of the oral cavity.In the longterm it can lead to a lack of sensitivity and sense of taste receptor changes and suppressthe salivary reflex.People with smokingchanges the value of the degree of acidity (pH) saliva.A research showed that smoking can make the pH of the saliva can becomemore acidic. Smoking habits can interfere with the function of the salivary glands and result in a decrease in salivary flow rate.The decrease in the flow rate of saliva has another impact on the oral cavity. These include caries, increased plaque accumulation,difficulty swallowing and chewing food, and teeth becoming more sensitive. The effects on the mucosa include mucositis,mucosal atrophy, and oral candidiasis.